Caffeine ameliorates metabolic-associated steatohepatitis by rescuing hepatic Dusp9 - Xin Xin; Cheng Chen; Xiao Xu; Sheng Lv; Qinmei Sun; Ziming An; Yi Chen; Zhekun Xiong; Yiyang Hu; Qin Feng (Redox Biology)
Caffeine (CAFF) is abundant in black coffee. As one of the most widely consumed beverages globally, coffee has been the focus of increasing clinical and basic research, particularly regarding its benefits in alleviating metabolic dysfunction-associated steatotic liver disease (MASLD). However, the therapeutic effects of CAFF on metabolic-associated steatohepatitis (MASH) and the underlying mechanisms remain unclear. In this study, we demonstrated that CAFF potently reduced hepatic steatosis, inflammation, and early-stage liver fibrosis in MASH mice induced by prolonged (36 weeks) high-fat high-carbohydrate (HFHC) diets and high-fat diets combined with carbon tetrachloride (CCl4) injections. By using multiple target-identifying strategies, including surface plasmon resonance (SPR), cellular thermal shift assay (CETSA), and drug affinity responsive target stability (DARTS) assay, we identified dual-specificity phosphatase 9 (Dusp9) as a key therapeutic target, which was diminished by HFHC but restored with CAFF treatment. Dusp9 knockdown in vivo and in vitro exacerbated glycolipid metabolism disorders and stunningly counteracted the systemic therapeutic effects of CAFF in the MASH models. In addition, CAFF inactivated the ASK1-p38/JNK, a downstream signaling pathway of Dusp9, which regulates inflammation and apoptosis. Our study highlights the multifaceted benefits of CAFF in treating MASH by rescuing hepatic Dusp9 expression, thereby reversing glycolipid metabolism disorders, liver inflammation, and fibrosis. These findings provide experimental evidence supporting the clinical and daily use of CAFF and black coffee in managing MASH patients.